Requirements and Challenges for Profitable Practice Implementation by Smallholder Farmers - Sodyna Soeurm; Mardy Serey (Yayasan Adra Karima Hubbi, 2024)
Alternative Wetting and Drying (AWD), practiced by some in rice farming, is one approach where water use efficiency can be improved and gaseous emissions mitigated while productivity is maintained. However, it also involves intermittent irrigation, allowing the fields to dry out before re-irrigation, as opposed to continuous flooding. They discovered that it is possible to reduce water use by around 25–30% while increasing rice yields by improving root growth and tiller production. Researchers have also discovered that AWD offers significant environmental advantages, such as a 50% reduction in methane emissions. Even though AWD has good potential, smallholders face many challenges when implementing it. These issues stem from the stability of food yields, insufficient knowledge, and restricted access to available infrastructure or technology. Moreover, farmers are hesitant to switch from traditional methods due to concerns that it could be a high-risk activity and involve labor-intensive water management chores. In addition, AWD needs both dependable water delivery infrastructure and monitoring equipment that often do not exist in remote or resource-constrained regions. For the widespread adoption of AWD, we must implement capacity-building initiatives alongside policy backing and investments in irrigation infrastructure. We address the benefits and challenges of AWD for small farmers who want to explore sustainable rice farming.